Species composition and structure of Angke Kapuk Mangrove Protected Forest, Jakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rumondang AL, Kusmana C, Budi SW. 2021. Species composition and structure of Angke Kapuk Mangrove Protected Forest, Jakarta, Indonesia. Biodiversitas 22: 3863-3871. Angke Kapuk Mangrove Protected Forest (AKMPF) is one of the protected forests in the coastal area of DKI Jakarta, Indonesia. This area is important for the north coast of Jakarta, hence it has function to protect the land from sea abrasion, seawater intrusion, and seawater flooding. This study aims to determine the condition of forest structures and species composition in the Angke Kapuk Mangrove Protected Forest (AKMPF) to obtain useful information for sustainable mangrove forest management. Vegetation data were collected using the sampling unit of transect for tree and line plot for forest regeneration inventories. Those data were analyzed for the density, frequency, dominance, species diversity, and species distribution pattern. The obtained results show that AKMPF consists of 13 mangrove species, including 7 species of true mangrove, 5 species associated mangrove, and 1 species of palm, with the dominant species, are Avicennia marina for tree with its regenerations and Acrostichum aureum for groundcover. Overall, the species diversity index in this area was classified as low category. Mangrove trees in this area have height class between 4-28 meters formed bell-curve, while stem diameter class were between 10.00-69.75 cm formed L-curve. The distribution pattern of species in this areal generally was clumped.
Keywords: Angke Kapuk Mangrove Protected Forest; forest structure; species composition; species distribution pattern